PATHOLOGICAL SIGNS OF EPILEPTIC AND NON-EPILEPTIC ORIGIN DETECTED IN AWAKE/SLEEP EEG PATTERNS DURING OUTPATIENT AND INPATIENT MONITORING: PROBLEMS OF INTERPRETATION - V. V. Gnezditskiy; O. S. Korepina; V. A. Karlov; G. B. Novoselova (Эпилепсия и пароксизмальные состояния, 2017)
The aims of this study were: (a) to elucidate the role of prolonged computerized EEG in assessing the brain function in patients with focal lesions (stroke consequences, tumor, etc.), and (b) to summarize the experience of using outpatient and inpatient EEG monitoring in neurological practice.Materials and methods. The study included 99 patients with post-stroke and other focal lesions or with a neurological deficit (aphasia, paresis, etc.) or with focal slow-wave and paroxysmal (epileptiform) activity, or with suspected «epilepsy». The patients were monitored using the method of ECG in outpatient and / or neurological hospital settings. The diagnosis of symptomatic epilepsy was confirmed in 81 patients (86%), and not confirmed – in 13 patients (14%). The patients’ age ranged from 16 to 78 years (average 56); the male/female ratio was 37/57.Results. The outpatient and impatient Holter EEG monitoring revealed various EEG patterns both in norm and pathology. Among those: different epileptiform signs (detected in all groups of patients) with different occurrence rates: PLEDs – rhythmic delta, frontal – FIRDA, temporal – TIRDA, spikes and complexes on the left and / or right, generalized paroxysms and photosensitivity. Examples of these EEG patterns (awake and sleep) are presented. Of special interest is the epileptiform pattern where polyspikes are combined with K complexes in the 2nd stage of sleep. Both generalized and focal patterns – mostly typical for sleep EEG – are demonstrated. The method of multiple dipole localization (MDL) was used to directly localize the sources of the abnormal EEG activity (slow-wave and paroxysmal) in the brain. In this report, combined results of EEG and MRI indicating the sources of the abnormal electrical activity are presented to compare the localization of the spike activity with that of the rhythmic slow waves. Two major causes of functional deficiency in post-stroke aphasia and plegia (and similar disorders) are proposed. Firstly, it is the presence of an ischemic focus with a decreased cerebral blood flow in this zone that results in a focal slow-wave activity (delta focus). Secondly, a loss of function can be caused by a continuous discharge activity of brain neurons. An epileptogenic focus and a continuous paroxysmal activity can lead to over-stimulation of brain neurons.Conclusion. Monitoring and analyzing EEG indicators in outpatients significantly expand the capabilities of EEG and provide new information on the brain function. In respect to the differential diagnosis between epileptic and non-epileptic seizures, prolonged monitoring allows to obtain additional information from EEG records and better identify epilepsy-associated activities.